1998
DOI: 10.1177/108835769801300306
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Social Stories to Reduce Precursors to Tantrum Behavior in a Student with Autism

Abstract: This study analyzed the effects of social stories in reducing precursors to tantrum behavior in two social environments, morning work time and lunchtime. The student was a 12-year-old boy diagnosed with autism, Fragile X syndrome, and intermittent explosive disorder. Using an ABAB design, two social stories were implemented and withdrawn as data were collected to determine the frequency of two behaviors, inappropriate vocalizations and dropping to the floor, which served as precursors to tantrum behavior. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 25 publications
3
91
0
1
Order By: Relevance
“…The literature and data indicate children with ASDs are predominantly visual learners (Kuttler et al, 1998;Grandin, 2006) and ICT can support the Social Story TM approach by including visual information to enhance meaning. An analysis of interviews and responses suggested that four out of seven carers believed social stories incorporating animation were best suited to the learning style of the children as the interactive features of animated characters could hold a child"s attention and were 'attractive and interesting' (Parent 6).…”
Section: [Figure 8]mentioning
confidence: 99%
See 2 more Smart Citations
“…The literature and data indicate children with ASDs are predominantly visual learners (Kuttler et al, 1998;Grandin, 2006) and ICT can support the Social Story TM approach by including visual information to enhance meaning. An analysis of interviews and responses suggested that four out of seven carers believed social stories incorporating animation were best suited to the learning style of the children as the interactive features of animated characters could hold a child"s attention and were 'attractive and interesting' (Parent 6).…”
Section: [Figure 8]mentioning
confidence: 99%
“…Visual cues (Kuttler et al, 1998;Grandin, 2006) and sound effects (Grandin, 2006;Attwood, 2007) are used to highlight important details as for instance in the activity Calling 9-9-9.…”
Section: [Figure 4]mentioning
confidence: 99%
See 1 more Smart Citation
“…Los autores informan de los resultados positivos para la enseñanza de nuevas habilidades y la disminución de conductas disruptivas (Swaggart et al, 1995); sin embargo, con esta intervención no podemos saber sólo el impacto relativo de las historias sociales (Gray, 1998). En el mismo área de trabajo conductual, Kuttler, Myles y Carlson (1998) obtuvieron buenos resultados a propósito del efecto de las historias sociales en reducir los precursores de las rabietas de un niño con autismo de 12 años. Incluso se han trabajado con éxito historias sociales a partir de un formato multimedia con 3 niños con autismo con una edad de educación elementaria para el aprendizaje de nuevas conductas (para una revisión, ver Bakken y Bock, 2001).…”
Section: Sistemas Visualesunclassified
“…A study by Kuttler et al (1998) showed a decrease in inappropriate behavior of students who tend to drop onto the floor, namely the behavior of rampage when social story intervention was performed. Similarly they did the same thing even when the intervention was withdrawn.…”
Section: Literature Reviewmentioning
confidence: 99%